Ovarian Tissue Culture to Preserve Fertility in Transgender Male Patients after Hormonal Treatment - Bottini, Alessandra Leal; Reis, Vânia Marisia Santos Fortes dos; Capp, Edison; Silva, Ilma Simoni Brum da; Kliemann, Lúcia Maria; Corleta, Helena von Eye (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To evaluate the reproductive and histological characteristics of fresh cultured ovarian tissue from transgender male patients.Methods An in vitro pilot study in which samples were collected during sex reassignment surgery for transgender male patients. The ovarian cortex was cut into fragments of 2 mm, 3 mm, and 4 mm, and placed in a 96-well plate suitable for cultivation at days 0, 2, 4, 6, and 8, when the histology was analyzed.Results Stromal hyperplasia was observed in all samples, and it was not associated with the obtainment of primordial or primary follicles. Peripheral reduction in cell count was also a recurrent finding. Primordial and primary follicles were identified with a heterogeneous pattern in fragments from the same patient and from different patients, and follicles in more advanced stages of development (secondary and antral) were not found. There was an association between the diameter of the ovarian fragments and the identification of primary follicles (p = 0.036). The number of days in culture was associated with histological signs of tissue damaging in the fragments (p = 0.002). The total number of follicles identified in the samples with 2 mm in diameter was significantly lower than in those that measured 4 mm in diameter (p = 0.031).Conclusion A diameter of 4 mm is suitable for ovarian tissue culture with the benefit of ease of handling. Even after prolonged exposure to testosterone, the ovarian fragments presented primordial and primary follicles, maintaining viability throughout the days they were exposed to the culture. Freezing the ovarian cortex of transgender patients who will undergo surgery for gender reassignment would be an interesting option, in the future, for the preservation of fertility.
Keywords: ovary; ovarian reserve; fertility preservation; tissue culture techniques; gender reassignment surgery